2009
DOI: 10.1111/j.1442-2018.2009.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of complementary therapy from the perspective of Thai women with breast cancer

Abstract: A qualitative study based on Heideggerian phenomenology was conducted with 17 Thai women who had survived breast cancer and had utilized at least one type of complementary therapy. The study explored the meaning of such therapy and the data were collected by an in-depth interview, a demographic data-recording form, and a reflective journal. The data were analyzed by using an interpretative process that was described by Cohen, Kahn, and Steeves. Six themes were generated in relation to the meaning of complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 20 publications
0
10
0
9
Order By: Relevance
“…Some researchers have used quantitative methods to explore the prevalence, effects, and costs of using CAM [3,8,9], whereas others have used qualitative research methods to determine the reasons for CAM use [11,12]. There is a dearth of information about the use of CAM for patients with TBI, a condition that usually occurs following a head injury after sustaining an accident.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have used quantitative methods to explore the prevalence, effects, and costs of using CAM [3,8,9], whereas others have used qualitative research methods to determine the reasons for CAM use [11,12]. There is a dearth of information about the use of CAM for patients with TBI, a condition that usually occurs following a head injury after sustaining an accident.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed in the existence of 700 species that can act on malignant tumors. 4 The mind-body interventions, in turn, as the prayer of healing, faith 3,18,38,[40][41][42] and meditation 18,24,38,[40][41]44 are also cited with common practices in cancer treatment . In general, regarding the professional performance in the face of PICs, it is observed that the doctor, pharmacist, psychologist and nurse are the closest professional practices, 31 although they have limited knowledge, 17 which requires greater skill in this perspective.…”
mentioning
confidence: 99%
“…Thus, such a paradigm innovates when highlights for professional humanistic values, altruistic, spiritual, scientific, existential and raisers of basic care. 46 Thus, the theoretical and practical improvement of the profession is essential,, 4,30,36,40 and that measures glimpsing this perspective should be planned and implemented in order to qualify nursing professionals to work in the perspective of PICs.…”
mentioning
confidence: 99%
See 2 more Smart Citations